Virtual Screening Attributes Male Biased COVID-19 Mortality to Predicted Antiviral Activity of Female Sex Hormones - Yahya, Galal; Mansour, Basem; Keuper, Kristina; Shaldam, Moataz; El-Baz, Ahmed M. (Letters in Drug Design & Discovery, 2021)
Background: Coronavirus disease-19 (COVID-19) is a newly emerged pandemic leading to a state of international alert and leaving millions of infections and thousands of deaths all over the world. Analysis of statistics and epidemiological data for the pandemic outcome pinpointed a puzzling influence of human sex on the heterogeneous outcome of COVID-19, where hospital admissions and mortality were higher among males than females. Two theories explained the observed male-biased COVID-19 mortality based on either dosage of immunoregulatory genes coded in X- chromosomes, or on the abundance of the angiotensin-converting enzyme two (ACE2) receptors in males than females. Objective: In our study, we propose a third scenario through virtual screening of direct antiviral effects of sex hormones. Materials and Methods: Updated screening statistics from 47 countries displaying sex-disaggregated data on COVID-19 were employed and visualized in the form of heatmaps depicting sex difference effects on statistics of cases and deaths. Molecular docking and binding simulations of investigated sex steroids against COVID-19 specific proteins were investigated. Results: Analysis of COVID-19 sex-disaggregated data confirmed that male-biased mortality and computer-aided docking found unexpected female sex hormones biased binding against key targets implicated in the life cycle of COVID-19 compared to the male sex hormone testosterone. Other investigated steroids showed promising docking scores, while the male sex hormone exhibited the lowest affinity. Conclusion: Female sex hormones virtually exhibit direct anti-COVID-19 effect, the proposed antiviral effect of sex hormones should be considered to explain the outcomes of mortality. Moreover, the fluctuation of sex hormones influences sex and personal derived-differential response to COVID-19 infection.
Keywords: COVID-19